Prenatal diagnosis of fetal right ventricular diverticulum with massive pericardial effusion in one of monochorionic diamniotic twins: a case report with a favorable outcome following in utero pericardiocentesis - Wang, Yunan; Liu, Chang; Yin, Aihua; Zhao, Xin; He, Wei; Xiong, Ying; Fang, Liyuan; Wu, Jing (Journal of international medical research, 2021)
Background Congenital ventricular diverticulum is a rare abnormality that may occur as an isolated malformation. Most cases are accompanied by pericardial effusion. Prenatal counseling can be difficult because the prognosis is uncertain and there is no consensus approach to prenatal management. Case presentation: We describe a case of congenital cardiac diverticulum complicated by large pericardial effusion in one of monochorionic diamniotic twins. The case was diagnosed by ultrasonography at 21 weeks of gestation. Therapeutic pericardiocentesis at 22 weeks resulted in complete resolution of the effusion and led to a favorable fetal outcome. We summarize the interventions and pregnancy outcomes in cases of cardiac diverticula reported in the literature. Conclusions Better awareness of clinical features, in utero therapies, and pregnancy outcomes could help define and improve prenatal management of congenital ventricular diverticula.